PEMANFAATAN LANGSUNG TEKNOLOGI INFORMASI DALAM DAKWAH ISLAM - Kurniawan, Fachrul (ULUL ALBAB Jurnal Studi Islam, 2012)
Information technology is evolving so fast these days, like all science also changes following the pace of information technology development, and this is simply due to the development of information technology continue to be done by making use of all existing science. In the world of Islam is often made use of information technology and one of them is used to preach. Today the world of preaching often use information technology to facilitate direct communication between the congregation and resource persons. Not to mention the use of interactive multimedia to further his message. This mission can we find a model like ESQ (Emotional Spiritual Quotient), which is the dominant technology. Data on the use of information technology as a medium of propagation is also seen seen from pegguna Islamic features that can be accessed via the internet, the statistics (Effective Measure) internet users in Indonesia reached 39.1 million (8 world ranking) if taken alone the percentage of 50% to access Islamic features of the 20 million people who use information technology as a medium of preaching both corporately and individually. And utilization of information technology in the world of preaching will increase when there are moments like the Ramadan month.Â